Integrated decision making for predictive maintenance of belt conveyor systems. (August 2019) - Liu, Xiangwei; He, Daijie; Lodewijks, Gabriel; Pang, Yusong; Mei, Jie
Highlights: A framework of integrated maintenance decision making is prompted. Reliability and condition monitoring data are integrated and interacted. Threshold value of a monitoring parameter varies in the framework. The framework results in more accurate maintenance decision making. Abstract: Belt conveyor systems are widely utilized for continuous transport of bulk materials. Maintenance activities are essential to ensure the reliability of belt conveyor systems. Conventional diagnosis decision is achieved based on empirical constant thresholds. The Challenge of this study is to propose a framework of integrated maintenance decision making for belt conveyor idlers. Information from operational conditions, reliability estimation of idlers and condition monitoring data are integrated for accurate decision making. Innovatively, in the proposed framework threshold of the monitoring parameter can vary according to real time operational conditions and reliability estimation results. A simulation study is presented to demonstrate the effectiveness of framework. Simulation results show that the framework can result in more accurate maintenance decision making compared to conventional approaches. Graphical abstract: Image, graphical abstract